1981
DOI: 10.1038/bjc.1981.224
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of some growth characteristics and cell-surface properties of neoplastic cells

Abstract: Summary.-Tumour cells from a polyoma-induced ascitic tumour were fractionated on the basis of the electrical charge on the cell surface by free-flow electrophoresis. Several characteristics of tumour cells have been investigated: (1) differences in the proliferation and antigenicity within the tumour at any point in time; (2) variation in proliferative potential with the ageing of the tumour.In early ascitic tumours, electrophoretically fractionated cells exhibit very similar proliferative characteristics. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this previous study the charge effect was found to be of larger magnitude but in the same direction as the present study, with the polycationic PIC having 6 times the uptake and 10 times the phototoxicity of the polyanionic PIC. This difference in magnitude between charge effects may be attributed to differences in the magnitude of the negative charge expressed on the outside of the cells (Bischoff et al, 1981), or to differences in the extent to which polycations stimulate endocytosis between cell lines (Duncan et al, 1979). It is accepted that imparting cationic charge to a protein 24.5 ± 1.31…”
Section: Discussionmentioning
confidence: 99%
“…In this previous study the charge effect was found to be of larger magnitude but in the same direction as the present study, with the polycationic PIC having 6 times the uptake and 10 times the phototoxicity of the polyanionic PIC. This difference in magnitude between charge effects may be attributed to differences in the magnitude of the negative charge expressed on the outside of the cells (Bischoff et al, 1981), or to differences in the extent to which polycations stimulate endocytosis between cell lines (Duncan et al, 1979). It is accepted that imparting cationic charge to a protein 24.5 ± 1.31…”
Section: Discussionmentioning
confidence: 99%